Superior metabolic improvement of polycystic ovary syndrome traits after GLP1-based multi-agonist therapy - Sánchez-Garrido, Miguel A.; Serrano-López, Víctor; Ruiz-Pino, Francisco; Vázquez, María Jesús; Rodríguez-Martín, Andrea; Torres, Encarnación; Velasco, Inmaculada; Rodríguez, Ana Belén; Chicano-Gálvez, Eduardo; Mora-Ortiz, Marina; Ohlsson, Claes; Poutanen, Matti; et al. (Springer Science and Business Media LLC, 2025)
Polycystic ovary syndrome (PCOS) is a heterogeneous condition, defined by oligo-/anovulation, hyper-androgenism and/or polycystic ovaries. Metabolic complications are common in patients suffering PCOS, including obesity, insulin resistance and type-2 diabetes, which severely compromise the clinical course of affected women. Yet, therapeutic options remain mostly symptomatic and of limited efficacy for the metabolic and reproductive alterations of PCOS. We report here the hormonal, metabolic and gonadal responses to the glucagon-like peptide-1 (GLP1)-based multi-agonists, GLP1/Estrogen (GLP1/E), GLP1/gastric inhibitory peptide (GLP1/GIP) and GLP1/GIP/Glucagon, in two mouse PCOS models, with variable penetrance of metabolic and reproductive traits, and their comparison with metformin. Our data illustrate the superior efficacy of GLP1/E vs. other multi-agonists and metformin in the management of metabolic complications of PCOS; GLP1/E ameliorates also ovarian cyclicity in an ovulatory model of PCOS, without direct estrogenic uterotrophic effects. In keeping with GLP1-mediated brain targeting, quantitative proteomics reveals changes in common and distinct hypothalamic pathways in response to GLP1/E between the two PCOS models, as basis for differential efficiency. Altogether, our data set the basis for the use of GLP1-based multi-agonists, and particularly GLP1/E, in the personalized management of PCOS.